Integrated bank analysis and valuation : a practical guide to the ROIC methodology - Chen, Sandy; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
Leading analyst Sandy Chen provides a thorough guide to the analysis and valuation of banks. Unlike other businesses and institutions, banks have a number of unique characteristics that need to be taken into account when performing a valuation and as such traditional valuation methodologies are unsuitable and more specialized techniques required.
Keywords: Science